Information and Communication Technology Utilization and Principals’ Administrative Effectiveness in Kwara State - Aliyu, Shehu Ahmed; Olasinde, Biliks Ajoke; Sadiq, Hummukhair Mopelola (International Journal of Educational Management, 2021)
This study focused on information and communication technology compliance in secondary schools and its implication on principals’ administrative effectiveness in Kwara State. Descriptive survey method was adopted in carrying out this research study. The target population for the study was all the principals in public secondary schools in Kwara State. Ten schools were selected from ten local government areas using purposive sampling technique while simple random sampling technique was employed to select principals who served as respondents to the questionnaire. The instrument used for this study was a 10-item questionnaire on four –point likert scale and was validated and subjected to reliability test. Two hypotheses were formulated and tested using Pearson product moment correlation statistical method at 0.05 level of significance. The study revealed that there was significant relationship between ICT utilization and principals administrative effectiveness. The study therefore recommended that secondary school principals should be ICT driven to meet the present day administrative challenges and that ICT facilities should be used for keeping records in schools due to the high increase in students enrolment in secondary schools in Kwara State.